Hand-suture versus stapling for closure of loop ileostomy: HASTA-Trial : a study rationale and design for a randomized controlled trial - Löffler, Thorsten; Seiler, Christoph; Rossion, Inga; Kijak, Thomas; Thomusch, Oliver; Hodina, Renè; Krüger, Matthias; Simon, Thomas; Bruckner, Thomas; Kieser, Meinhard; Büchler, Markus W.; Weitz, Jürgen (Trials, 2011)
Colorectal cancer is the second most common tumor in developed countries, with a lifetime prevalence of 5%. About one third of these tumors are located in the rectum. Surgery in terms of low anterior resection with mesorectal excision is the central element in the treatment of rectal cancer being the only option for definite cure. Creating a protective diverting stoma prevents complications like anastomotic failure and meanwhile is the standard procedure. Bowel obstruction is one of the main and the clinically and economically most relevant complication following closure of loop ileostomy. The best surgical technique for closure of loop ileostomy has not been defined yet.